A Whole Transcriptome Analysis in Peripheral Blood Suggests That Energy Metabolism and Inflammation Are Involved in Major Depressive Disorder - Wang, Yu; Wei, Jinxue; Chen, Ting; Yang, Xiao; Zhao, Liansheng; Wang, Min; Dou, Yikai; Du, Yue; Ni, Rongjun; Li, Tao; Ma, Xiaohong (Frontiers in Psychiatry, 2022)
Introduction: Previous studies on transcriptional profiles suggested dysregulation of multiple RNA species in major depressive disorder (MDD). However, the interaction between different types of RNA was neglected. Therefore, integration of different RNA species in the analysis of transcriptome would be helpful for interpreting the functional readout of transcriptome in MDD. Methods: We performed whole transcriptome sequencing on peripheral blood of 15 patients with MDD and 15 matched healthy controls (HCs). The differential expression of miRNA, lncRNA, circRNA and mRNA was examined between MDD and HCs using empirical analysis of digital gene expression data in R (edgeR). The weighted correlation network analysis (WGCNA) was used to identify RNAs co-expression modules that associated with MDD. A ceRNA network was constructed for interpretation of interaction between different RNA species. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were conducted to explore potential biological mechanism associated with MDD. Results: We identified 7 miRNAs, 25 lncRNAs, 16 circRNAs, 956 mRNA transcripts and 4 co-expression modules that were significantly dysregulated in MDD compared to HCs. The ceRNA network indicated that 7 ceRNAs might bind to 14 miRNAs and regulate 33 mRNAs expression. We also identified two pathway networks associated with MDD, which were related to oxidative phosphorylation and chemokine signaling pathway, respectively. Conclusion: Our results suggested the processes of energy metabolism and inflammation may be involved in pathophysiology of MDD.